Stock Valuation- Incorporating New Measures into the Traditional Methods - Zhai, Junyi (2013)
This study investigate the specific factors which impact on corporate stock performance which is measured by stock return in the US companies from 2009 to 2012, aims to examine the relationship between firms` environmental performance and stock performance and discuss the way to incorporate environmental performance into stock valuation process. The results report the dividend yield and overall green score have negative impact on stock performance, and return on invested capital, environmental impact score, the green policies score and the reputation have positive impact on stock performance in the model of this study, and the P/E ratio, return on equity and cash flow/sales ratio have no relationship with stock performance. The result implies that environmental performance do impact on stock performance which is in line with the expectation. Finally this paper provide a analysis about how the environmental affect the stock performance which include short-term and long-term period and discuss the way to take corporate environmental performance into account while valuing a stock, provide a more comprehensive and reliable way for stock valuation process.